2019
DOI: 10.1111/geer.12176
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Control Assessment of the Green Paradox: The Role of Climate Action Plans

Abstract: This paper extends the green paradox literature by providing empirical insights into its existence. To check the green paradox theory, I analyse the production of coal in four major coal‐producing US states that announced a greenhouse gas action plan. To form a statement on whether there is a treatment effect caused by the green policy, I employ Synthetic Control Methods to calculate counterfactual coal production trajectories. I find that Montana experienced a high and statistically significant increase in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Zhang et al (K. Zhang, Zhang, & Liang, 2017) found that although implementing environmental policies promoted the reduction of carbon emissions, government fiscal decentralization led to the increase of carbon emissions, which led to the confirmation of the green paradox hypothesis. Arne Steinkraus (Steinkraus, 2019) evaluates the effect of the US Environmental Action Plan policy. The discovery policy announcement led to a significant increase in coal production in the United States, triggering the "green paradox" effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhang et al (K. Zhang, Zhang, & Liang, 2017) found that although implementing environmental policies promoted the reduction of carbon emissions, government fiscal decentralization led to the increase of carbon emissions, which led to the confirmation of the green paradox hypothesis. Arne Steinkraus (Steinkraus, 2019) evaluates the effect of the US Environmental Action Plan policy. The discovery policy announcement led to a significant increase in coal production in the United States, triggering the "green paradox" effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is growing literature on the causal impacts of action plans in the context of energy, green economy, climate change, etc. Steinkraus [ 2 ] used the climate action plans of several US states as a case study to estimate causal impacts on coal production. Similarly, Kim & Kim [ 3 ] evaluated the Regional Greenhouse Gas Initiative implemented in several US states.…”
Section: Introductionmentioning
confidence: 99%
“…(2016) explored the tragedy of the commons in resource exploitation and ecosystem service depletion in the Amazon estuary [9]. Some experts also tried to verify the effectiveness of environmental regulations, while the green paradox implied the promotion of environmental regulation may not achieve the original intention of policymaking [10,11]. However, many experts said it depended on different countries' situations.…”
Section: Introductionmentioning
confidence: 99%